Anthony William Linnane. 17 July 1930—11 November 2017. (14th December 2019) - Nagley, Phillip
Abstract : Anthony (Tony) Linnane isolated mitochondria from bakers' yeast during his doctoral studies at the University of Sydney in the 1950s. He subsequently pioneered research into the biogenesis of mitochondria, covering enzymology, membrane biochemistry and molecular biology and genetics, over more than two decades until the mid 1980s. These discoveries were made mostly at Monash University and earned him election as a Fellow of the Australian Academy of Science (FAA 1972) and of the Royal Society (1980). Linnane thereafter broadened his research towards medical topics, especially the role of mitochondria in human ageing, together with studies on interferon and cancer-specific mucinous antigens. After retirement from Monash in 1996, Linnane worked towards ameliorating disease through bioenergetic strategies, based at the Centre for Molecular Biology and Medicine in Melbourne. He played significant roles in the Australian Biochemical Society and the International Union of Biochemistry. Note: This memoir was commissioned by the Historical Records of Australian Science and is published here with minor amendments. It was published in May 2019 and is available at https://doi.org/10.1071/HR19001 . Additional supplementary material is available at this site.